Demographic transition and population ageing - Wan Ahmad, Wan Ibrahim (MCSER Publishing, Rome-Italy, 2015)
This article discusses the findings of a literature review on older persons globally. In recent years the number of older persons aged 60 years and older is growing worldwide.Declining in birth and mortality rates are said to be the main contributors to this new phenomenon.Life expectancy of general population has also increased, and thus the number of older population in society increased.Although all nations in the world are experiencing the growth of older population, developed countries has a relatively large portion of this population in their population structure.The purpose of this article is analyzing the process of demographic transistion that produces the growth of older person world wide.In particular, it describes the growth of older population globally with particular emphasis on the proportion of older population over the years, distribution of older population, and rate of growth of this older population.By using a secondary analysis, various sources related to older persons at international level are reviewed.This paper highlights that the proportion of older population has increased, it has distributed unevently, and the growth rate of older population is higher as compared to the growth of the total population globally.